Effect of continuous progressive resistance training during hemodialysis on body composition, physical function and quality of life in end-stage renal disease patients: a randomized controlled trial - Costa Rosa, Clara Suemi da [UNESP]; Nishimoto, Danilo Yuzo [UNESP]; Damasceno e Souza, Giovana [UNESP]; Ramirez, Ariane Pereira; Carletti, Carla Oliveira; Lombardi Daibem, Celio Guilherme; Sakkas, Giorgos K.; Monteiro, Henrique Luiz [UNESP] (Sage Publications Ltd, 2018)
Objective: This study aimed to investigate the effect of continuous progressive resistance training on body composition, functional capacity and self-reported quality of life in end-stage renal disease patients. Design: A randomized controlled trial. Subjects: The study included 52 hemodialysis patients (aged 55.714.03years) randomized into exercise (progressive resistance training (PRT), n=28) or control (CON, n=24) groups. Intervention: Patients randomized into the PRT group received prescribed strength exercises in two sets of 15-20 repetitions, in a repetition maximum training zone regime, thrice a week for 12weeks, during hemodialysis. Patients randomized into the CON group received a sham-exercise with active mobilization of the arms and legs without load and progression. Main outcome measure: Body composition using dual-energy X-ray absorptiometry (DXA), strength using handgrip dynamometry (HGS), repeated sit-to-stand test (STT), 6-minute walk test, flexibility and the SF-36 questionnaire (quality of life (QoL)) were assessed at baseline and at 12weeks. Results: Leg lean mass (P=0.04, effect size (ES) of 0.56), bone mineral content (P=0.02, ES of 0.65), leg strength in STT repetitions (P=0.01, ES of 0.66) and flexibility (P<0.01, ES of 1.03) were significantly improved in the PRT group compared to the CON group. Walking capacity, HGS and QoL were not different between the groups. Conclusion: 12weeks of PRT with a repetition maximum training zone regime provided significant load to increase leg lean mass and STT performance as well as bone mineral content, compared to the CON, which continued to deteriorate. There was lack of efficacy on walking test, HGS and QoL.
Keywords: Renal failure; hemodialysis; strength training; physical capacity; exercise